Design of an Information System for Regulation and Survey of Small and Medium Enterprises (SMEs) at the Community and Village Empowerment Service of Gunungsitoli City - Harefa, Yusmei Paskah; Lase, Devi Chrisman; Gulo, Aperianto; Zendrato, Bowoaro (Jurnal Teknologi Informatika dan Komputer, 2025)
In today's digital era, the use of information technology in the government sector has become an urgent need to improve efficiency, transparency, and public services. Globally, digital transformation in the public sector is encouraging governments in various countries to build technology-based systems to strengthen governance and public participation (Nurkartika, 2025). In the context of the ever-growing digital transformation of government, the need for adaptive and responsive information systems is essential, especially in managing regulations and conducting public satisfaction surveys. This study aims to design and implement a web-based Regulatory Information System and Public Satisfaction Index (IKM) Survey at the Gunungsitoli City Community and Village Empowerment Service (DPMD). The software development method used is Waterfall, including the stages of needs analysis, design, implementation, testing, and maintenance. In the implementation process, the system was built using the CodeIgniter 3 framework and SBAdmin template, with PHP, HTML, and CSS programming languages, and a MySQL database. Testing was carried out using the Blackbox Testing method and showed that all main features of the system, such as regulatory management, IKM survey input, and report generation, functioned validly. These results confirm that the system is capable of supporting agency operational efficiency, increasing public transparency, and strengthening the principles of good governance. Thus, this research not only contributes to improving the quality of public services, but also opens up opportunities for developing similar systems in other government agencies.